2000
DOI: 10.1007/bf01279902
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes during early embryogenesis in wheat pollen

Abstract: Summary.We have made a detailed cytological examination of the development of wheat embryoids, monitoring their initial divisions from two to ten cells by both light and electron microscopy. According to our observations the first embryogenic division is symmetrical. After the androgenesis induction treatment, there is a decrease in ribosome population with cells that have inactive nucleoli made up almost exclusively of a dense fibrillar component. This population is restored after initial embryogenic division… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Similar results were obtained earlier in callus that was derived from Citrus sinensis , which showed that cells that were destined to form new proembryoids became surrounded by greatly thickened cell walls without PD 95 . An analysis of androgenesis in Zea mays and Triticum aestivum also showed that cells that realize the same developmental program are connected by numerous intercellular connections 96 , 97 …”
Section: Zygotic and Non-zygotic Embryogenesis—a Good Model For Symplasmic Communication Studiessupporting
confidence: 72%
“…Similar results were obtained earlier in callus that was derived from Citrus sinensis , which showed that cells that were destined to form new proembryoids became surrounded by greatly thickened cell walls without PD 95 . An analysis of androgenesis in Zea mays and Triticum aestivum also showed that cells that realize the same developmental program are connected by numerous intercellular connections 96 , 97 …”
Section: Zygotic and Non-zygotic Embryogenesis—a Good Model For Symplasmic Communication Studiessupporting
confidence: 72%
“…In cereals, microspores are polarized due to the presence of a single round aperture in the pollen wall. In agreement with this observation, in cereals, early embryogenic multicellular structures contained within the exine are often characterized by two heterogeneous cell domains; a smaller domain comprised of small, dense cells and a larger domain comprised of larger cells (Bonet and Olmedilla 2000; Dubas et al 2010; Góralski et al 2005; Magnard et al 2000; Maraschin et al 2005b; Testillano et al 2002). In maize, the large domain shows similarity to endosperm, including a coenocytic organization with incomplete cell walls, synchronous cell division, vacuolated cytoplasm and starch granules (Testillano et al 2002).…”
Section: Polarity Establishment and Histodifferentiationmentioning
confidence: 75%
“…Localized vesicular secretion is essential for remodeling of the cell wall and for the establishment of polarization in Fucus and has also been shown to be important in vascular plants for polar transport of the morphogen hormone auxin (Belanger and Quatrano 2000; Geldner et al 2003). The cell wall changes that characterize the switch to microspore embryogenesis, include the moderate growth of the innermost pecto-cellulosic wall and intine (Bonet and Olmedilla 2000; Schulze and Pauls 2002; Solís et al 2008; Telmer et al 1995), an increase in pectin esterification (Bárány et al 2010) and the differential localization of arabinogalactan epitopes (El-Tantawy et al 2013). These or other changes in the cell wall properties could be important for the ability of induced microspores to develop into embryos and require further study.…”
Section: Polarity Establishment and Histodifferentiationmentioning
confidence: 99%
“…Zheng and Ouyang (1980) reported that cold pre-treatment induces symmetrical division in wheat microspores. However, in wheat anther culture, Hassawi et al (1990) report that the first division of microspores is asymmetric, unlike in the culture of isolated microspores in which the first division (after 3 d of culture) is symmetrical (Bonet and Olmedilla 2000). In triticale, the stress signal used has been cold pretreatment of spikes that contain microspores at the miduninucleate stage (Charmet and Bernard 1984, González et al 1997, Tuvesson et al 2000, but until now, no studies had been performed to determine the type of division induced in the microspores.…”
Section: Discussionmentioning
confidence: 95%